2023
DOI: 10.52722/pcej.v5i1.588
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Silica Fume dan Pecahan Batu Marmer Sebagai Bahan Subtitusi Pada Campuran Beton

Abstract: Tujuan penelitian untuk mengetahui pengaruh penggunaan silica fume dan pecahan batu marmer sebagai bahan subtitusi pada campuran beton pada kuat tarik belah, kuat lentur beton dan kuat tekan. Pengujian benda uji yakni kuat tarik belah, kuat lentur, dan kuat tekan. Pada penelitian ini direncanakan mutu beton yaitu 25 MPa.Dari  hasil penelitian diperoleh nilai kuat tekan beton untuk variasi pecahan batu marmer sebesar 50% dan Silica Fume 0%, 10%, 12,5% dan 15% yaitu sebesar 25,175 MPa, 25,832 MPa, 24,606 MPa dan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
0
0
Order By: Relevance
“…The value of silica fume substitution was highest in the 10% variation, but the strength of concrete decreased if the percentage of silica fume substitution was higher. [7]. The results showed that the use of silica fume and coral shard ash in concrete can have an impact on the strength of concrete.…”
Section: Introductionmentioning
confidence: 95%
“…The value of silica fume substitution was highest in the 10% variation, but the strength of concrete decreased if the percentage of silica fume substitution was higher. [7]. The results showed that the use of silica fume and coral shard ash in concrete can have an impact on the strength of concrete.…”
Section: Introductionmentioning
confidence: 95%
“…Batuan atau mineral yang termasuk golongan ini, mempunyai sifat-sifat fisik tertentu yang menarik, sehingga dapat digunakan sebagai bahan perhiasan atau dekorasi. Batu mulia digunakan di berbagai industri batu permata, dan sebagai bahan perhiasan atau asesoris/dekorasi (Faizin et al, 2019); (Alfrian et al, 2021); (Debi et al, 2021); (Papendang et al, 2023); (Sarasanty & Zulfika, 2021); (Buli et al, 2022); (Julmile et al, 2023); (Garinas, 2020); (Kabir et al, 2018); (Solechan & Kiswanto, 2018).…”
Section: Pendahuluanunclassified
“…In other studies using marble waste as an ingredient in concrete mixtures has also been developed. According to Elli Mercy Julmile et al [12] That the effect of using silica fume and marble stone fragments as substitution materials in concrete mixtures on split tensile strength, flexural strength of concrete and compressive strength. With a design concrete quality of 25 MPa.…”
Section: Introductionmentioning
confidence: 99%